Between old and new unionism: Race, professionalism, and resistance in a district of market reforms - Kurtz, Erin; White, Terrenda (Education Policy Analysis Archives, 2022)
This article centers a group of teachers who participated in a multi-day strike and a statewide walkout in Colorado. We examine whether their experience with contention signaled important shifts in views of market-based educational policies, teacher professionalism and the role of unions. Qualitative methods and critical theories of educational policy guided the research design and analysis of data. Findings include divergent experiences with contention among teachers, shaped by race and racism, and enduring ideas of professionalism tied to hierarchies of class and gender. These tensions complicated coherent interpretations and critiques of market policies and strained solidarity for sustained resistance. We discuss the implications of findings for efforts to shift traditional teacher unions toward expansive ideas of professionalism premised on anti-racism, collective action, and social justice for and with communities of color.